ANALISIS TREN PENJUALAN PRODUK HANDBODY TYZA MENGGUNAKAN REGRESI LINEAR SEDERHANA - Suwanti, Ratih; Ayu, Sri (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the sales trend of the TYZA Handbody product, a personal business established in 2022 in Gowa, South Sulawesi. The business focuses on selling whitening handbody products through both online and in-store channels. This research employs a quantitative method with data collection techniques including questionnaires and documentation. Data analysis was carried out using simple linear regression with the assistance of SPSS. The results show that sales experienced a consistent upward trend from the first to the fifth month, with a significant increase occurring in the sixth and seventh months. The regression equation obtained was Yt = 60.857 + 53.750X, which was used to forecast sales trends from the eighth to the twelfth month. The predictions indicated a steady increase in sales, providing a valuable basis for future marketing strategy decisions. This research offers useful insights for business owners to make data-driven decisions and maximize business growth opportunities.